1998
DOI: 10.1177/107906329801000304
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Histories and Fantasies of Youthful Males: A Comparison of Sexual Offending, Nonsexual Offending, and Nonoffending Groups

Abstract: The present clinical and theoretical literature suggests that adolescents' sexual histories and fantasies are factors contributing to the onset and perpetuation of criminal sexual behaviors. However, few data exist either to support or to refute such assertions. The purpose of the present study was to describe the self-reported sexual histories and fantasies of four groups: 104 incarcerated adolescent sexual offenders between 10 and 15 years of age, 198 16- to 20-year-old incarcerated sexual offenders, 124 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 12 publications
1
43
1
3
Order By: Relevance
“…Prior research, however, is problematic; inferential statistics are sometimes missing, fantasies of male children and adults are combined, fantasies of rape are combined with fantasies of pain or subsumed within broader 'deviant' categories, and comparison groups sometimes have a sexual offending history [9,20]. Other studies include only one comparison [10,13,14,21] or no comparison [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research, however, is problematic; inferential statistics are sometimes missing, fantasies of male children and adults are combined, fantasies of rape are combined with fantasies of pain or subsumed within broader 'deviant' categories, and comparison groups sometimes have a sexual offending history [9,20]. Other studies include only one comparison [10,13,14,21] or no comparison [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, prior research has used long fantasy checklists [e.g. 9,10,17,20], providing insights into the prevalence of fantasies but nothing about their nature. Each checklist item is presented as a separate, discrete fantasy (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of deviant behavior, Daleiden, Kaufman, Hilliker, and O'Neil (1998) suggested that fantasy content may be less relevant for supporting deviant acts than other factors, such as the intrusive and automatic nature of deviant sexual thoughts. Recently, Cortoni and Marshall (2001) provided some support for this position.…”
Section: Introductionmentioning
confidence: 98%